2019
DOI: 10.1097/sla.0000000000003512
|View full text |Cite
|
Sign up to set email alerts
|

Defining Global Benchmarks in Bariatric Surgery

Abstract: OBJECTIVE To define "best possible" outcomes for bariatric surgery (BS)(Roux-en-Y gastric bypass [RYGB] and sleeve gastrectomy [SG]). BACKGROUND Reference values for optimal surgical outcomes in well-defined low-risk bariatric patients have not been established so far. Consequently, outcome comparison across centers and over time is impeded by heterogeneity in case-mix. METHODS Out of 39,424 elective BS performed in 19 high-volume academic centers from 3 continents between June 2012 and May 2017, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“… ** ***** Dallal, 2008 [ 27 ] ** ** *** ******* Garg, 2016 [ 40 ] *** . ** ***** Gero, 2019 [ 41 ] *** . *** ****** Gribsholt, 2016 [ 32 ] *** ** *** ******** Inabnet, 2011 [ 33 ] *** ** ** ******* Kellogg, 2009 [ 26 ] *** .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… ** ***** Dallal, 2008 [ 27 ] ** ** *** ******* Garg, 2016 [ 40 ] *** . ** ***** Gero, 2019 [ 41 ] *** . *** ****** Gribsholt, 2016 [ 32 ] *** ** *** ******** Inabnet, 2011 [ 33 ] *** ** ** ******* Kellogg, 2009 [ 26 ] *** .…”
Section: Resultsmentioning
confidence: 99%
“…The indications for readmissions and number of readmissions are presented in Table 6 . Four studies showed indications for readmissions [ 26 , 32 , 40 , 41 ]. The different timepoints of FU have shown similar reasons for readmissions in which abdominal pains, intestinal obstruction, gastrointestinal complaints including nausea and vomiting, and dietary complaints were most common.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Etwa 4 % der operierten Patienten werden aufgrund eines postoperativen Problems (Wundinfekt, Thrombose, Lungenembolie, Darmpassageproblematik etc.) innerhalb von 30 Tagen erneut hospitalisiert, die 30-Tage-Letalität beträgt 0,05-0,2 % [8]. Unter Berücksichtigung des anästhesiologischen und chirurgischen Risikoprofils dieser Patientenklientel sind diese Zahlen auch im Vergleich zu anderen viszeralchirurgischen Eingriffen insgesamt sehr niedrig.…”
Section: Komplikationenunclassified